IMPLEMENTASI SISTEM ERP MENGGUNAKAN APLIKASI ODOO DI IWEAR CLOTHING - Prabowo, Dimas Aditya; Agun Guntara; Irfan Fadil (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2026)
The implementation of an integrated information system has become a crucial need in addressing business challenges, especially for SMEs such as Iwear Clothing. This study aims to implement an ERP system using the Odoo application to overcome business process problems that were previously carried out manually. The research method used is the Agile method with a Scrum framework and a phased implementation approach. Data collection was conducted through observation, interviews, and documentation. The implementation results indicate that the developed ERP system successfully improves production efficiency, stock accuracy, and simplifies sales and financial data recording. The main modules implemented include Manufacturing, Inventory, Sales, and Invoicing. The system also enhances decision-making processes and reduces data entry errors. This study concludes that Odoo as an ERP platform can be effectively adopted by small-scale garment businesses to support more structured and integrated operations. The implementation of an integrated information system has become a crucial need in addressing business challenges, especially for SMEs such as Iwear Clothing. This study aims to implement an ERP system using the Odoo application to overcome business process problems that were previously carried out manually. The research method used is the Agile method with a Scrum framework and a phased implementation approach. Data collection was conducted through observation, interviews, and documentation. The implementation results indicate that the developed ERP system successfully improves production efficiency, stock accuracy, and simplifies sales and financial data recording. The main modules implemented include Manufacturing, Inventory, Sales, and Invoicing. The system also enhances decision-making processes and reduces data entry errors. This study concludes that Odoo as an ERP platform can be effectively adopted by small-scale garment businesses to support more structured and integrated operations.